1997
DOI: 10.1006/qres.1997.1929
|View full text |Cite
|
Sign up to set email alerts
|

Geochronology of Middle and Upper Pleistocene Loess Sections in Hungary

Abstract: The application of both thermoluminescence and infrared stimulated luminescence dating to the extensively studied “classical” Hungarian loess/paleosol sequences from Basaharc, Mende, and Paks provides a reliable chronological framework and climatostratigraphic reconstruction for the last interglacial/glacial cycle. Based on this combined luminescence dating study a new chronology is proposed for the “Young Loess” in Hungary. Luminescence dating suggests that the loess below the MF2 horizon formed during the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
73
1
11

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 18 publications
10
73
1
11
Order By: Relevance
“…He dated also some of the profiles described in this paper but the results seem to be incomparable with modern ones. The results of TL dating carried out in Lublin in the years 1980-1992 differ also from the results obtained for the same loess profiles in other TL laboratories (Butrym, 1987;Butrym and Maruszczak, 1984;Frechen et al, 1997).…”
Section: History Of the Tl Laboratory In Lu-blincontrasting
confidence: 77%
See 3 more Smart Citations
“…He dated also some of the profiles described in this paper but the results seem to be incomparable with modern ones. The results of TL dating carried out in Lublin in the years 1980-1992 differ also from the results obtained for the same loess profiles in other TL laboratories (Butrym, 1987;Butrym and Maruszczak, 1984;Frechen et al, 1997).…”
Section: History Of the Tl Laboratory In Lu-blincontrasting
confidence: 77%
“…This is caused by long bleaching by artificial light, which can change the sensitivity of mineral material. This phenomenon does not occur in every dated sample, however the obtained results should be verified using the total-bleach technique (Berger et al, 1992;Frechen, 1992 andFrechen et al, 1997 andZhou and Wintle, 1994), which is free from the above-mentioned limitations.…”
Section: Luminescence Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…Early TL chronologies from the DLPS (e.g. Wintle, 1987;Singhvi et al 1989) were obtained using protocols which have since been shown to be potentially unreliable in loess environments (Frechen et al, 1997). Subsequently, optically stimulated luminescence dating (OSL) on quartz, and infrared stimulated luminescence dating (IRSL) on feldspars and polymineral samples dominated by feldspar signals were adopted and thought to provide more reliable age estimates (Balescu et al 2003(Balescu et al , 2010Novothny et al 2009Novothny et al , 2010Lang et al 2003;Timar et al 2010).…”
mentioning
confidence: 99%